Review on Ferulic Acid in Cosmaceuticals - Kashish; Ritika Saini; Abhinav Singh Badhopal; Aayush Rao; Samridhi Dogra; Abhinav Kaushal (Recent Trends in Cosmetics, 2026)
Ferulic acid is low in toxicity and possesses a variety of physiological qualities, including anti- inflammatory, antioxidant, antibacterial, anticancer, and antidiabetic effects. Science has demonstrated that ferulic acid, a potent antioxidant, has beneficial benefits on skin care. In addition to preventing pigmentation and whitening the skin, ferulic acid also prevents acne. Ferulic acid which is a strong natural antioxidant is necessary in protecting the skin against oxidative stress caused by the free radicals. It suppresses the total oxidative injury as it is a free radical scavenger and an inhibitor of significant enzymes which generate reactive oxygen species. Also, ferulic acid enhances the numbers of scavenger enzymes and activates endogenous antioxidant defense system in the body by improving cellular defense.
Keywords: Cosmeceuticals; Ferulic acid; Skin care; UV protection; antioxidant